Large Aggressive Angiomyxoma of the Liver: A Case Report and Brief Review of the Literature - Sun, Pi-Jiang; Yu, Yan-Hua; Cui, Xi-Jun (Frontiers in Oncology, 2019)
Aggressive angiomyxoma (AAM) is an uncommon mesenchymal myxoid tumor that almost solely involves the soft tissues of the perineum and pelvis. An AAM originating from the liver is extremely rare. Herein, we present a case of a 45-year-old female with a large mass in the left lateral lobe of the liver. She underwent a left lateral lobe hepatectomy. The histopathology of the resected specimen showed features that were characteristic of AAM. Immunohistochemical analysis of the neoplastic cells showed reactions to antibodies against CD34, smooth muscle actin (SMA), and Ki67 (2%) and showed no reactions to antibodies against Estrogen receptor (ER), C-keratin (CK), and Desmin. The patient was subsequently diagnosed with a primary AAM of the liver. This is the largest AAM of the liver that has been reported. We hereby report these findings and review the current literature.